2016
DOI: 10.1002/chem.201600386
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation and Transfer Hydrogenation Promoted by Tethered Ru−S Complexes: From Cooperative Dihydrogen Activation to Hydride Abstraction/Proton Release from Dihydrogen Surrogates

Abstract: Hydrogenation and transfer hydrogenation of imines with cyclohexa-1,4-dienes, as well as with a representative Hantzsch ester dihydrogen surrogate, are reported. Both processes are catalyzed by tethered Ru-S complexes but differ in the activation mode of the dihydrogen source: cooperative activation of the H-H bond at the Ru-S bond leads to the corresponding Ru-H complex and protonation of the sulfur atom, whereas the same cationic Ru-S catalyst abstracts a hydride from a donor-substituted cyclohexa-1,4-diene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 60 publications
1
31
0
1
Order By: Relevance
“…The thus‐generated diastereomeric chiral‐at‐ruthenium hydrosilane adducts were applied to catalytic imine hydrosilylation but enantioinduction (40 % ee ) was at best promising. One challenge could be that there is no bonding interaction between the neutral ruthenium hydride and the silyliminium ion in the enantioselectivity‐determining hydride transfer . This work is nevertheless proof of concept for asymmetric catalysis involving cooperative Si−H bond activation.…”
Section: Resultsmentioning
confidence: 89%
“…The thus‐generated diastereomeric chiral‐at‐ruthenium hydrosilane adducts were applied to catalytic imine hydrosilylation but enantioinduction (40 % ee ) was at best promising. One challenge could be that there is no bonding interaction between the neutral ruthenium hydride and the silyliminium ion in the enantioselectivity‐determining hydride transfer . This work is nevertheless proof of concept for asymmetric catalysis involving cooperative Si−H bond activation.…”
Section: Resultsmentioning
confidence: 89%
“…[32] Heterolytic cleavage of the Si À Hb ond at the metal-sulfur bond of these complexes results in the formation of as ulfur-stabilized silicon cation and ar uthenium hydride (XVII!XVIII, Scheme 11,bottom). XX is known to be unstable at room temperature, [31] immediately releasing dihydrogen to reform XVII. Thes uccess of these steps for Friedel-Crafts silylation hinges on the Lewis basic sulfur atom in complex XIX,w hich acts as an internal base,a bstracting the proton from Wheland intermediate XII (XII!XIII and XIX!XX).…”
Section: Catalysis Involving Metalsmentioning
confidence: 99%
“…Afew years ago,Oestreich in collaboration with Ohki and Tatsumi found that cooperative Si À Hb ond activation at Lewis acidic metal centers is an entry into catalysis with electrophilic silicon reagents, [29,30] for example,f or Friedel-Crafts silylation. [29] Oestreich and co-workers used Ohki-Tatsumi complexes,c oordinatively unsaturated ruthenium thiolate complexes initially applied to dihydrogen activation, [31] for this purpose (38,S cheme 11, top). [32] Heterolytic cleavage of the Si À Hb ond at the metal-sulfur bond of these complexes results in the formation of as ulfur-stabilized silicon cation and ar uthenium hydride (XVII!XVIII, Scheme 11,bottom).…”
Section: Catalysis Involving Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…B. für Friedel-Crafts-Reaktionen, bietet. [29] Oestreich und Mitarbeiter nutzten zu diesem Zweck Ohki-Tatsumi-Komplexe, also koordinativ ungesättigte Rutheniumthiolatkomplexe,die ursprünglich zur Diwasserstoffaktivierung verwendet worden waren [31] (38,S chema 11, oben). [32] Die heterolytische Spaltung der Si-H-Bindung an der Metall-Schwefel-Bindung resultiert in der Bildung eines schwefelstabilisierten Siliciumkations und eines Rutheniumhydrids (XVII!XVIII,S chema 11, unten [31] und bildet unter sofortiger Diwasserstofffreisetzung wieder XVII.…”
Section: Katalyse Unter Beteiligung Von Metallenunclassified